Rara & rarissima : documenting the fringes of linguistic diversity - Wohlgemuth, Jan; Cysouw, Michael (Empirical approaches to language typology ;, 2010)
The papers in this book describe and analyze rara in individual languages, covering an extraordinarily broad geographic distribution, including papers about languages from all over the globe. The range of theoretical subjects discussed shows an enormous breadth, ranging from phonology through word formation, lexical semantics to syntax and even some sociolinguistics.